Risk of breast implant associated anaplastic large cell lymphoma (BIA-ALCL) in a cohort of 3546 women prospectively followed long term after reconstruction with textured breast implants. Issue 5 (May 2020) - Cordeiro, Peter G.; Ghione, Paola; Ni, Andy; Hu, Qunying; Ganesan, Nivetha; Galasso, Natasha; Dogan, Ahmet; Horwitz, Steven M.
Summary: Background: The risk of BIA-ALCL for patients with textured breast implants has been estimated between 1/2832 and 1/30, 000 women. Existing studies estimating the numbers exposed and at risk, may have under reported cases, and/or lacked comprehensive follow-up. Our objective is to determine the risk of BIA-ALCL in a defined cohort of patients reconstructed with macro-textured breast implants and consistently followed long-term. Methods: A prospective cohort study was conducted in patients who underwent breast reconstruction by a single surgeon at Memorial Sloan Kettering Cancer Center (MSKCC) from December 1992 to December 2017. Major events related to implants were prospectively recorded. We identified cases of BIA-ALCL by cross-checking clinical, pathology and external records data. Patients were followed until lymphoma occurrence or last follow-up. The primary outcomes were incidence rate per person-years and cumulative incidence. Results: From 1992 to 2017, 3546 patients underwent 6023 breast reconstructions, mainly after breast cancer removal, or contralateral prophylactic mastectomy, using macro-textured surface expanders and implants. All reconstructions were performed by a single surgeon (PGC). Median follow-up was 8.1 years (range, 3 months – 30.9 years). Ten women, 1/354, developed ALCL after a median exposure of 11.5 years (range, 7.4–15.8 years). Overall risk of BIA-ALCL in our cohort is 1/355 women or 0.311 cases per 1000 person-years (95% CI 0.118 to 0.503). Discussion: This study, the first to evaluate the risk of macro-textured breast implants from a prospective database with long term follow-up, demonstrates that the incidence rate of BIA-ALCL may be higher than previously reported. These results can help inform implant choice for women undergoing breast reconstruction.